Intraoperative Margin Control in Eyelid Tumor Surgery: Current Standards, Imaging Advances, and Emerging Techniques. - Nardella, Michele; Argentesi, Anna; Pirro, Claudia; Leoni, Claudia Quaranta; Leoni, Francesco M. Quaranta (Current Oncology, 2026)
Simple Summary: Eyelid tumors require highly precise surgical management because the eyelids play a critical role in protecting the ocular surface, and their delicate structures must be preserved whenever possible. The primary challenge is to achieve complete tumor removal while minimizing injury to surrounding healthy tissue. Specialized intraoperative techniques enable surgeons to evaluate surgical margins in real time and confirm that no malignant cells remain. Among these methods, Mohs micrographic surgery is widely considered the gold standard because of its high cure rates and maximal tissue conservation. Frozen section-controlled excision is another suitable approach, particularly in settings where Mohs surgery is not available. Emerging imaging technologies, including confocal microscopy, optical coherence tomography, photoacoustic imaging, and artificial intelligence–assisted analysis, may further enhance surgical precision and efficiency. Over time, these advances could broaden access to high-quality care, lower recurrence rates, and support more personalized treatment strategies. Background: Eyelid malignancies require accurate intraoperative margin control to achieve complete tumor excision while preserving the functional and aesthetic integrity of the periocular region. Mohs micrographic surgery (MMS) is widely regarded as the reference standard for margin-controlled excision, whereas frozen section–controlled excision (FSC) represents a reliable and widely used alternative in oculoplastic practice. In parallel, several emerging imaging technologies are being investigated to improve real-time tumor detection and surgical precision. Methods: A narrative review of the literature was conducted to summarize current evidence on intraoperative margin control in eyelid tumor surgery. The review focused on established surgical techniques, including MMS and FSC, as well as emerging imaging modalities such as fluorescence confocal microscopy, reflectance confocal microscopy, optical coherence tomography, line-field confocal optical coherence tomography, photoacoustic imaging, and artificial intelligence (AI)-assisted analysis. Results: MMS provides complete circumferential peripheral and deep margin assessment and remains the benchmark for high-risk, recurrent, and poorly defined periocular tumors, particularly basal cell carcinoma. FSC offers favorable oncologic outcomes, allows immediate reconstruction, and remains an effective option when MMS is not available. Emerging imaging modalities have shown promising diagnostic performance for tumor detection, presurgical mapping, and intraoperative support, particularly in basal cell carcinoma, although evidence in periocular tumors remains limited for most techniques. AI-assisted approaches have also demonstrated high accuracy in the interpretation of frozen sections and optical imaging data, suggesting potential to improve workflow efficiency and diagnostic consistency. Conclusions: MMS and FSC remain the current standards for intraoperative margin control in eyelid tumor surgery. Emerging imaging technologies and AI-based tools may further enhance surgical precision and tissue preservation, but most remain investigational in the periocular setting. Further prospective studies are needed to validate their clinical utility, define standardized workflows, and clarify their role alongside established histopathologic techniques.